FINANCING MECHANISMS FOR INVESTMENT PROJECTS IN THE AGRICULTURAL SECTOR OF UKRAINE'S ECONOMY INVOLVING ANGEL INVESTORS - T. Nagachevska; V. Zakharchenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The challenges connected with attracting foreign investments into the agricultural sector of the Ukrainian economy as well as diversification of forms of international investments are actual due to the immediate needs of realization of innovative development, technological upgrading and strengthening of agricultural sector attractiveness on the world market. Current situation and problems connected with attracting foreign investments into the agricultural sector of the Ukrainian economy are revealed. It is detected that level of attracting foreign investments into the agricultural sector of Ukraine and into AIC together don't meet the needs of its innovative potential. The following factors of agricultural sector attractiveness have been considered: high soil fertility and favorable weather conditions for growing crops; export capacity; high yield of the Ukrainian farming companies; undervalued assets and low level of capitalization of agricultural companies; attractive tax regime for agricultural producers. It is recommended that agricultural producers should indicate these factors in investment proposals and projects that they present to potential international investors. State investment policy in the agricultural sector is viewed to consolidate the resource base and the sources of investment have been determined. Suggestions to expand the financing mechanisms for investment projects in the agricultural sector involving angel investors have been justified. Economic feasibility of attracting foreign investments for financing of innovation activity of farming companies has been revealed. The key requirements and main stages of investments of angel investment association have been described.